2020
DOI: 10.3389/fnins.2020.00115
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Schizophrenia and Depression Comorbidity as One Psychiatric Disorder Entity: Evidence From Mouse Model

Abstract: Schizophrenia is frequently accompanied by depressive symptoms, but the pathological mechanisms remain to be elucidated. In this study, we used chronic unpredicted mild stress plus MK801 injection to generate a mouse model of schizophrenia with depression, in which in vivo 2-photon calcium imaging and electrophysiological recordings were performed in conjunction with behavioral phenotyping. Compared to mice models with classical depression or to schizophrenia models, the animal models with schizophrenia and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…In the current study previous suicide attempts had an impact on the Calgary scores. This was also reported by Zhou et al 11 who found that lifetime suicide is common among hospitalized patients with schizophrenia living in agricultural areas of China.…”
Section: Screening For Depression Among Schizophrenia Patients Discussionsupporting
confidence: 79%
“…In the current study previous suicide attempts had an impact on the Calgary scores. This was also reported by Zhou et al 11 who found that lifetime suicide is common among hospitalized patients with schizophrenia living in agricultural areas of China.…”
Section: Screening For Depression Among Schizophrenia Patients Discussionsupporting
confidence: 79%
“…Data were compared using one-way analysis of variance and post hoc Tukey tests. Data analysis and figure plotting were performed with the GraphPad Prism software (version 8.0) [ 65 , 66 ]. No animals were excluded from the present study.…”
Section: Methodsmentioning
confidence: 99%
“…We recently modeled coexistent schizophrenia and depression by exposing mice to chronic unpredictable mild stress (CUMS) after receiving 10-day exposures to MK801. Behavioral assays showed higher despair, anhedonia and deficits of prepulse inhibition (PPI) (Zhou et al, 2020). This model of schizophrenia with comorbid depression thus provides a valuable tool for in vivo drug evaluation.…”
Section: Introductionmentioning
confidence: 94%